1990
DOI: 10.1007/bf00000601
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum geochemistry in peatland waters

Abstract: Abstract. The chemical speciation of aluminum was examined in surface water samples from Sphagnum peatlands in north-central Minnesota, from peatlands along the Canadian east coast, and from bogs in the Pennine Mountain area of England. In highly organic ([DOC] x 50 mg L-'), low pH waters, 80-90% of total dissolved Al was complexed with organic matter (OM), while in waters with low DOC ([DOC] x 5 mg L-') 5446% of total dissolved A1 existed as Al+' or other inorganic Al species. Batch titrations of OM with Al r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…Elevated concentrations of Al coincided with the high H 2 concentrations around 100 cm (>300 lmol L À1 ) and 210 cm depth (150 lmol L À1 ) (electronic annex Fig. 3), which is much higher than generally observed in surface or pore-water in peatlands (Helmer et al, 1990) and could thus account for a limited production rate in these depths. Depending on its speciation, aluminum species are highly toxic to aquatic organisms (Gensemer and Playle, 1999), but information on their influence on methanogenic and fermentative bacteria does not seem available.…”
Section: Constraints On Decompositionmentioning
confidence: 88%
“…Elevated concentrations of Al coincided with the high H 2 concentrations around 100 cm (>300 lmol L À1 ) and 210 cm depth (150 lmol L À1 ) (electronic annex Fig. 3), which is much higher than generally observed in surface or pore-water in peatlands (Helmer et al, 1990) and could thus account for a limited production rate in these depths. Depending on its speciation, aluminum species are highly toxic to aquatic organisms (Gensemer and Playle, 1999), but information on their influence on methanogenic and fermentative bacteria does not seem available.…”
Section: Constraints On Decompositionmentioning
confidence: 88%
“…Sequestration by DOC reduces adsorptive losses to solid surfaces and enhances metal transport from wetland sediment porewaters to streams. Al and Pb are representative of metals with a high affinity for DOC (Christensen et al 1999;Helmer et al 1990;Schnitze and Skinner 1967;Sposito 1986) and their association with DOC is supported by metal-DOC Pearson correlation coefficients for the stream and rivulet dataset (r = 0.86 and r = 0.74, respectively) while La (r = 0.55), Ce (r = 0.52) and Zn (r = 0.55) are also correlated with DOC. Concentrations of all five metals were 2-3 times higher in the streams in the spring, when DOM and associated inorganic colloids are flushed from the wetland (Fig.…”
Section: Metal Transport By Docmentioning
confidence: 97%
“…Helmer et al (1990) observed higher concentrations of dissolved aluminum in bogs than in fens (in North America and England), and Vitt et al (1995) also observed higher concentrations of dissolved aluminum and iron in a bog than in fens (in Canada). Helmer et al (1990) concluded that the concentrations of dissolved aluminum in bogs and fens are regulated by both the solubility of gibbsite and the concentration of DOC, because high concentrations (over 4 mM) of DOC facilitate formation of soluble aluminum-DOC complexes. Indeed, in Mizorogaike, when pond water sampled at station 2 in October 2001 (dissolved aluminum ϭ 0.44 µM, pH ϭ 6.5) was analyzed by the method of Sutheimer and Cabaniss (1995), 25% of the dissolved aluminum was present as organic complexes.…”
Section: Relationships Between Distributions Of Chemical Components Amentioning
confidence: 78%
“…Monthly variations in a pH, b dissolved organic carbon (DOC), c dissolved organic phosphorus (DOP), d dissolved Al, e dissolved Si, f dissolved Fe, g dissolved Mn, h PO 4 -P, i particulate Al, j particulate Si, k particulate Fe, l particulate Mn, and m particulate P in Mizorogaike pond. Two data points (station 7 in July, dissolved Al ϭ 10 µM; station 4 in August, PO 4 -P ϭ 1.29 µM) were out of range and are not shown Helmer et al (1990), Thormann et al (2001), BendellYoung andPick (1995), and Gorham et al (1985), as shown in Table 2. The solid line represents a regression line derived from this study ([DOC, mM] ϭ Ϫ 0.80 pH ϩ 5.8; r ϭ 0.85), and the broken line represents a regression line derived from data for other bogs ([DOC, mM] ϭ Ϫ 3.4 pH ϩ 17; r ϭ 0.83).…”
Section: Relationships Between Distributions Of Chemical Components Amentioning
confidence: 89%
See 1 more Smart Citation